Histori Piagam Jakarta: Spirit Perjuangan Penerapan Nilai Islam Secara Yuridis Konstitusional - Ariesman; Iskandar (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
The historical journey of Indonesian independence which has long been aspired by the nation's generation continues to be fought for, the role of Islamic figures and Islamic values ​​in coloring all aspects of community life in the archipelago between a strong foundation to be free from colonialism, because basically Islam is freedom from colonialism to beings to worship to the Creator. The process of Indonesian independence took place in several phases including Japan's victory over the Netherlands, the phase of the formation of the BPUPKI team, PPKI, to the process of proclamation of independence which resulted in the basis of the Indonesian State known as the "Jakarta Charter"